Exploring communication during the journey from noticing bodily changes to a diagnosis of endometrial cancer. Issue 5 (19th December 2017) - Cook, Catherine; Brunton, Margaret; Pukepuke, Tepora; Tan, Ai Ling
Abstract : Aims and objectives: To understand women's perspectives about the trajectory from first bodily changes to diagnosis. Background: With endometrial cancer, as with all gynaecological cancers, early diagnosis is key to successful outcomes. However, women do not always seek clinical advice early. Previously, this gap has been referred to as a "delay, " blamed on fear or refusal to acknowledge symptoms. Methods: A qualitative research project which involved face‐to‐face interviews with 16 women who had presented with symptoms of endometrial cancer. The paucity of research in the trajectory of women who experience a diagnosis of endometrial cancer required an exploratory overview of the data. Accordingly, an inductive thematic analysis was conducted using the framework of Braun and Clarke (Qualitative Research in Psychology, 3, 2006, 77). Results: Women and health professionals both resorted to satisficing, using heuristics to make decisions about the importance of symptoms depending on their severity and duration. Most women initially determined that the bodily changes were within the realms of normal. Time to diagnosis was also affected by the following: women's long‐standing assumptions; communication with health professionals; liminality—women oscillating between their self‐assessment that these changes were something significant or nothing important; and gaps in health literacy. Conclusions: The journey from noticing bodily changes to diagnosis was a nonlinear trajectory. Women worked to make sense of what was happening to them, informed by their sociocultural environment. In particular, confusion about the purpose of cervical screening led a number of participants who had regular smears to assume they were "safe" from cancer worries. Relevance to clinical practice: Women and some health professionals may be unfamiliar with symptoms potentially indicative of endometrial cancer. There may be structural and communication barriers for women navigating healthcare systems. It is vital that nurses take time both to listen to women and to provide them with resources to enhance their health literacy.